Surgical technique for knee osteoarthritis induction in New Zealand white rabbits - Abu Hassan, Salmah Anim; Zulkifly, Ahmad Hafiz; Abd. Rahim, Nour El Huda; Mohamad Amri, Nur Fathonah; Hassan, Habibah; Mohd Jan, Nurul Hafiza; Ibrahim, Mohd Zulfadzli; Mohd Zohari, Sarah Haryati; Zainal Abdullah, Muhamad Ezham; Che Seman, Che Nor Zarida; Abdul Hamid, Zahana; Abdul Jalil, Rosnani (Malaysian Orthopaedic Association, 2023)
INTRODUCTION: Osteoarthritis (OA) is a degenerative joint disease that affects both humans and animals. It is characterized by the progressive deterioration of the cartilage an underlying bone. Surgical techniques are often used in animal models of OA to study the disease progression.